The layout and the spatio-temporal evolution of water-polluting enterprises in Zhejiang under regulation - Xu, Xiaozhi; Zhang, Yu; Wu, Liou (Frontiers in Environmental Science, 2023)
Water pollution is closely related to the development of water pollution-intensive industries, but there is a lack of relevant research, and few studies to verify the existence of “pollution heaven”. This paper aims to study the layout and the spatio-temporal evolution of water-polluting enterprises. Taking Zhejiang Province, China as an example, this study visualized the spatial distribution of water pollution enterprises under the " Five Water Treatment " regulations during 2018-2022. At the same time, based on the Mann-Whitney U test, this paper verifies the hypothesis of pollution paradise in Zhejiang Province. The results show that the distribution of water pollution enterprises in Zhejiang is clustered, and water pollution control has been realized to a certain extent. However, water pollution enterprises still tend to be located in areas with lower environmental standards and weak environmental regulations. In view of this, the government should optimize the industry structure, strengthen the supervision of suburban water pollution enterprises.